2019
DOI: 10.1080/1343943x.2019.1647788
|View full text |Cite
|
Sign up to set email alerts
|

Ion accumulation and expression of ion homeostasis-related genes associated with halophilism, NaCl-promoted growth in a halophyte Mesembryanthemum crystallinum L.

Abstract: A halophyte, the common ice plant (Mesembryanthemum crystallinum L.), shows the maximal growth under salinity, in which almost all crops die. The NaCl-stimulated growth, which is referred to as halophilism, is an important trait for adaptation to salinity, but the mechanism is still unclear. To elucidate factors contributing to the halophilism, we tested the effects of NaCl on growth, ion accumulation, and expression of ion homeostasis-related genes in suspension-cultured cells. Among nine ions analyzed, Na + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Although microbial-mediated drought or heavy metal tolerance in plants [53,54] has been elucidated, our understanding of the salt tolerance mechanisms of EB remains lacking. A recent valuable work has proven that ion accumulation and the expression of ion homeostasis-related genes contribute to the NaCl-stimulated growth enhancement in halophytes, especially the common ice plant [18]. Nevertheless, the current study of Halomonas sp.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although microbial-mediated drought or heavy metal tolerance in plants [53,54] has been elucidated, our understanding of the salt tolerance mechanisms of EB remains lacking. A recent valuable work has proven that ion accumulation and the expression of ion homeostasis-related genes contribute to the NaCl-stimulated growth enhancement in halophytes, especially the common ice plant [18]. Nevertheless, the current study of Halomonas sp.…”
Section: Discussionmentioning
confidence: 89%
“…The analysis of novel gene responses of EB may provide a potential method to cope with salinity. EB can enhance Arabidopsis thaliana growth under salt stress and can tolerate high salt concentrations and show a potential competitive advantage of surviving in saline soils [18,19]. The complete genome sequence of the endophyte Bacillus flexus helps in revealing the plant growth-promoting mechanism of EB [20].…”
Section: Introductionmentioning
confidence: 99%
“… Putative salt tolerance mechanisms in an ideal halophyte plant (modified from Zhao et al [ 11 ], Arif et al [ 34 ], Arbelet-Bonnin et al [ 72 ], Tran et al [ 75 ], and Himabindu et al [ 76 ]. The absorption of Na + in plant cells is counterbalanced by active Na + extrusion through SOS1 Na + /H + exchanger ( I ).…”
Section: Physiological Mechanisms Associated With Halophyte Adaptation To Soil Salinitymentioning
confidence: 99%
“…On the other hand, factors that contribute to halophilism include ion (Na + , Cl À , K + , and NO 3À ) accumulation. Tran et al (2020) have observed significant accumulations of these ions in the cells of these plants (halophilism) that do not appear in cells without salt treatment. The accumulation of these ions was positively correlated with the growth.…”
Section: Xerohalophyte Speciesmentioning
confidence: 90%